Las Casas Filipinas de Acuzar the art of heritage hospitality - Daoana, Carlomar Arcangel; Radovan, Joey
On a sprawl measuring 400 hectares, between the fragrant rice fields of Bagac, Bataan and the threshing waters of West Philippine Sea, lies las Casas Filipinas de Acuzar. Houses, dating from 18th to 19th centuries, constellate on this recreated village of cobblestone streets, small plazas and outdoor sculptures, breathing new life and presenting refurbished dignity. Relocated from their original sites, they look at once curiously alike and radically different: powerful testimonies of the past, they meet at and diverge from various visual and architectural points and by extension, with the way they once kept and maintained domestic histories and human lives within their walls.